Advances in Cultural Linguistics - Sharifian, Farzad (Springer Singapore : Imprint: Springer, 2017)
This groundbreaking collection represents the broad scope of cutting-edge research in Cultural Linguistics, a burgeoning field of interdisciplinary inquiry into the relationships between language and cultural cognition. The materials surveyed in its chapters demonstrate how cultural conceptualisations encoded in language relate to all aspects of human life - from emotion and embodiment to kinship, religion, marriage and politics, even in the understanding of life and death. Cultural Linguistics draws on cognitive science, complexity science and distributed cognition, among other disciplines, to strengthen its theoretical and analytical interventions. The tools it has developed have worked toward insightful investigations into the cultural grounding of language in numerous applied domains, including World Englishes, cross-cultural/intercultural pragmatics, intercultural communication, Teaching English as an International Language (TEIL), and political discourse analysis.
Keywords: Social sciences.; Comparative linguistics.; Psycholinguistics.; Sociolinguistics.; Sociology.; Cognitive psychology.; elektronické knihy; electronic books